1969
DOI: 10.1139/z69-214
|View full text |Cite
|
Sign up to set email alerts
|

Studies of physiologically active arthropod secretions. III. Chemical, morphological, and histological studies of the defence mechanism of Uroblaniulus canadensis (Say) (Diplopoda:Julida)

Abstract: The defensive secretion of a millipede, Uroblaniulus canadensis (Say), is shown to consist of a mixture of benzoquinones and aliphatic compounds. Two of the benzoquinones are identified as p-benzoquinone and 2,3-dimethoxybenzoquinone. The gross structure of the gland producing the secretion is described and histological studies reveal the presence of secretory units. Each secretory unit consists of a pair of specialized cells and has a tubule to transport the secretion manufactured in these cells to a large cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

1974
1974
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…In addition, one hitherto undescribed compound, 2-methoxy-6-methyl-1,4-benzoquinone (compound F), was characterized from the defensive secretion. Julid species reportedly produce various 1,4-benzoquinones (Behal and Phisalix, 1900;Weatherston and Percy, 1969;Röper and Heyns, 1977;Eisner et al, 1978). Among them, the defensive secretion of a millipede, Uroblaniulus canadensis (Say), was shown to consist of a mixture of benzoquinones and unidentified aliphatic compounds (Weatherston and Percy, 1969).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, one hitherto undescribed compound, 2-methoxy-6-methyl-1,4-benzoquinone (compound F), was characterized from the defensive secretion. Julid species reportedly produce various 1,4-benzoquinones (Behal and Phisalix, 1900;Weatherston and Percy, 1969;Röper and Heyns, 1977;Eisner et al, 1978). Among them, the defensive secretion of a millipede, Uroblaniulus canadensis (Say), was shown to consist of a mixture of benzoquinones and unidentified aliphatic compounds (Weatherston and Percy, 1969).…”
Section: Discussionmentioning
confidence: 99%
“…Julid species reportedly produce various 1,4-benzoquinones (Behal and Phisalix, 1900;Weatherston and Percy, 1969;Röper and Heyns, 1977;Eisner et al, 1978). Among them, the defensive secretion of a millipede, Uroblaniulus canadensis (Say), was shown to consist of a mixture of benzoquinones and unidentified aliphatic compounds (Weatherston and Percy, 1969). In quinone-producing spirobolid species, an aliphatic compound from Rhinocricus insulatus has been characterized as trans-2-dodecenal (Wheeler et al, 1964), while uncharacterized components have been reported for two species, Narceus annularis and Floridobolus penneri (Monro et al, 1962).…”
Section: Discussionmentioning
confidence: 99%
“…The histology of the glands has not been studied very thoroughly; the most detailed work to date using light microscopy being that of Weatherston and Percy (1969). Woodring and Blum (1963) and Eisner et al (1963aEisner et al ( , 1963bEisner et al ( , 1993c examined Type 3 glands at a gross histological level.…”
Section: Histology Of the Glandsmentioning
confidence: 99%
“…What histological work has been done focuses on Type 2 glands. Weatherston and Percy (1969) found that the gland cells of Uroblaniulus canadensis (Julida, Parajulidae) were not continuous in lining the gland, but were interspersed among the hypodermal cells that secrete the procuticular lining of the gland. There appeared to be two types of gland cells arrayed in not more than about 20 pairs.…”
Section: Histology Of the Glandsmentioning
confidence: 99%
“…Along with (E)-2-dodecenal from Rhinocricus insulatus (Wheeler et al, 1964), this is the second record of the occurrence of (E)-2-alkenals in the secretions of juliform Diplopoda, and the first incidence of alkenals in the secretions of Julida. For other Juliformia, sporadic reports on nonbenzoquinone compounds are available, but these either deal with probably cuticle-derived components (e.g., Monro et al, 1962;Weatherston and Percy, 1969), or the identification of these components is only tentative and/or might need reconsideration. For example, analytical data for the identification of a putative alkaloid, 3,3a,4,5-tetrahydro-1H-pyrrolo-[2,3-b] pyridine-2,6-dione, from the secretion of R. padbergi are largely missing (Arab et al, 2003).…”
Section: Discussionmentioning
confidence: 99%